Pengaruh Manajemen Talenta Dan Motivasi Terhadap Prestasi Kerja Pegawai Pada Kantor Dinas Perumahan Rakyat,Kawasan Permukiman Dan Pertanahan Provinsi Sumatera Barat - Sumiati; Vilkades (CV. ITTC INDONESIA, 2022)
This study aims to analyze the effect of talent management and motivation on employee performance at the Rahyat Housing Office, Settlement and Defense Areas of West Sumatra Province. This study uses quantitative methods. The population is employees at the Office of the Rahyat Housing Office, Settlement and Defense Areas of West Sumatra Province, as many as 59 respondents and the sample is 59 respondents, the sampling technique is saturated sapling technique where all populations are sampled. Data analysis using multiple linear regression analysis using SPSS application. The results showed that talent management had a positive and significant effect on employee performance at the Rahyat Housing Office, Settlement and Defense Areas of West Sumatra Province, and work motivation had a positive and significant effect on employee performance at the Rahyat Housing Office, Settlement and Defense Areas of West Sumatra Province.